Liver resection in a patient with persistent positive PCR test for coronavirus disease 2019 (COVID-19): a case report - Akiho Sugita; Fuyuki F. Inagaki; Nobuyuki Takemura; Mai Nakamura; Kyoji Ito; Fuminori Mihara; Kei Yamamoto; Shinichiro Morioka; Norihiro Kokudo (Surgical Case Reports)
Abstract Background The perioperative mortality rate is high in patients with coronavirus disease 2019 (COVID-19), and infection control measures for medical care providers must be considered. Therefore, the timing for surgery in patients recovering from COVID-19 is difficult. Case presentation A 65-year-old man was admitted to a hospital with a diagnosis of moderate COVID-19. He was transferred to our hospital because of risk factors, including heavy smoking history, type 2 diabetes mellitus, and obesity (BMI 34). Vital signs on admission were a temperature of 36.1 °C, oxygen saturation > 95% at rest, and 94% on exertion with 3 L/min of oxygen. Chest computed tomography (CT) showed bilateral ground-glass opacities, predominantly in the lower lungs. Contrast-enhanced abdominal CT incidentally revealed a liver tumor with a diameter of 80 mm adjacent to the middle hepatic vein, which was diagnosed as hepatocellular carcinoma (HCC). After being administered baricitinib, remdesivir, dexamethasone, and heparin, the patient’s COVID-19 pneumonia improved, his oxygen demand resolved, and he was discharged on day 13. Furthermore, the patient was initially scheduled for hepatectomy 8 weeks after the onset of COVID-19 following a discussion with the infection control team. However, 8 weeks after the onset of illness, a polymerase chain reaction (PCR) test was performed on nasopharyngeal swab fluid, which was observed to be positive. The positive results persisted till 10 and 11 weeks after onset. Both Ct values were high (≥ 31) out of 45 cycles, with no subjective symptoms. Since we determined that he was no longer contagious, surgery was performed 12 weeks after the onset of COVID-19. Notably, medical staff wearing personal protective equipment performed extended anatomical resection of the liver segment 8 ventral area in a negative-pressure room. The patient had a good postoperative course, with no major complications, including respiratory complications, and was discharged on postoperative day 14. Finally, none of the staff members was infected with COVID-19. Conclusions We reported a case regarding the timing of surgery on a patient with persistently positive PCR test results after COVID-19, along with a literature review.